Clinical associations of the positive anti Ro52 without Ro60 autoantibodies: undifferentiated connective tissue diseases. Issue 1 (29th June 2017) - Murng, Sai H K; Thomas, Moira
Abstract : Aims: Autoantibodies targeting Ro52 and Ro60 antigens are historically reported as anti SSA/Ro. In general anti SSA/Ro results are either anti Ro52+Ro60+ or anti Ro52−Ro60+ antibodies. Anti Ro52 without anti Ro60 (Ro52+ Ro60−) antibodies are often not reported routinely. This study intends to review the potential significance of these autoantibodies in the management of connective tissue diseases. Method: A retrospective survey of Ro52+Ro60− was carried out as part of the service evaluation of extractable nuclear antigen antibodies (ENA) reporting from the immunology laboratory, the NHS Greater Glasgow and Clyde (GGC), UK. The clinical documents and laboratory results of 97 patients with Ro52+Ro60− and 100 patients with Ro52+Ro60+ were reviewed. Results: Seventy-one patients (73%) with anti Ro52+Ro60− antibodies have been diagnosed with autoimmune conditions including undifferentiated connective tissue diseases (n=14, 14%), systemic lupus erythematosus (n=10, 10%), Sjögren's syndrome (n=10, 10%) and rheumatoid arthritis (n=13, 13%). Twenty-three patients (24%) with anti Ro52+Ro60− antibodies have no autoimmune features but were found to have significant clinical conditions including malignancies. In contrast, 87 patients (87%) with anti Ro52+Ro60+ antibodies have autoimmune conditions including Sjögren's syndrome (n=34, 34%), systemic lupus erythematosus (SLE; n=23, 23%), undifferentiated connective tissue diseases (n=12, 12%) and rheumatoid arthritis (n=6, 6%). Conclusion: Anti Ro52 without anti Ro60 (Ro52+Ro60−) antibodies should be reported. In the majority of patients these autoantibodies were associated with various autoimmune diseases. Anti Ro52+Ro60− antibodies were also found in patients with significant clinical conditions including malignancies even though there was no suggestion of autoimmunity at the time of testing.